2007
DOI: 10.1530/eje-07-0428
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in ACTH -secreting and non-functioning pituitary tumors

Abstract: Objective: Differential expression of several genes between ACTH-secreting pituitary tumors causing Cushing' disease (CD), silent corticotroph adenoma (SCA), and non-functioning pituitary tumors (NFT) was investigated. Design and methods: We used tissue specimens from 35 pituitary tumors (12 CD, 8 SCA, and 15 NFT). Steady-state mRNA levels of the genes related to proopiomelanocortin (POMC) transcription, synthesis, processing, and secretion, such as neurogenic differentiation 1 (NeuroD1), T-box 19 (Tpit), cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 40 publications
5
94
0
2
Order By: Relevance
“…POMC mRNA levels were significantly higher in CD than in NFT, a finding consistent with that of a previous study by Tateno et al [8]. In the anterior lobe of the pituitary gland, POMC gene is expressed in ACTH-producing cells, and its expression is regulated by various transcription factors, such as Tpit and Nur77.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…POMC mRNA levels were significantly higher in CD than in NFT, a finding consistent with that of a previous study by Tateno et al [8]. In the anterior lobe of the pituitary gland, POMC gene is expressed in ACTH-producing cells, and its expression is regulated by various transcription factors, such as Tpit and Nur77.…”
Section: Discussionsupporting
confidence: 91%
“…Tateno et al [8] showed that POMC and Tpit mRNA levels were higher in CD than in non-functioning pituitary tumors (NFTs). PC1/3 mRNA levels were also higher in CD than in NFT.…”
Section: Hormonal Assaysmentioning
confidence: 99%
“…DAX-1, an orphan nuclear receptor, is also a cell-specific factor for gonadotroph cell differentiation [23] and is expressed in nonfunctioning adenomas [18]. SCAs have been shown by some groups to have similar Tpit expression to CD [20,58] while others demonstrate lower expression [10,52]. In one series, despite variable expression, POMC and TPIT mRNA levels correlated positively in SCAs, similar to the pattern in Cushing macroadenomas [43].…”
Section: Pathogenesismentioning
confidence: 68%
“…It has been reported that ACTH-secreting pituitary tumors show enhanced 11β-HSD2 gene expression but suppressed 11β-HSD1 gene expression [44,45]. Expression levels of 11β-HSD2 mRNA in the ACTH-secreting pituitary tumors that cause Cushing's disease were greater than those in SCAs [46], suggesting a partial or weak resistance by glucocorticoids in SCAs.…”
Section: Management and Follow Up Of Subclinical Cushing's Diseasementioning
confidence: 99%